2016
DOI: 10.1159/000455287
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Common Fragile Sites in Cancers with a Human Papillomavirus Etiology

Abstract: High-risk human papillomaviruses (HPVs) are known to be associated with different anogenital cancers including cervical, anal, penile, and vaginal cancers. They are also found to be responsible for the dramatic increases in oropharyngeal squamous cell carcinoma (OPSCC) observed in the United States and Europe. The model for how high-risk HPVs induce cancer formation comes from studies of cervical cancer which usually involves integration of the HPV into the human genome and subsequent changes due to induced ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 77 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…With the development of detection technology, new high-frequency integration sites are constantly found. Existing studies have reported that some Common Fragile Sites (CFS) widely exist in human chromosomes [18], which are often the common integration sites of various carcinogenic virus genes into the human genome including HPV. The reported CFS were 40, and two high-frequency integration sites in the study belong to CFS, such as CSMD1 and CDH13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of detection technology, new high-frequency integration sites are constantly found. Existing studies have reported that some Common Fragile Sites (CFS) widely exist in human chromosomes [18], which are often the common integration sites of various carcinogenic virus genes into the human genome including HPV. The reported CFS were 40, and two high-frequency integration sites in the study belong to CFS, such as CSMD1 and CDH13.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Chip Design and Order. We designed the sequencecapture probes according to 20 types of HPV genome (6,11,16,18,31,33,35,39,42,43,44,45,51,52,53,56,58,59, 66, and 68) sequences, and these probes were produced by Agilent Inc., USA. The enrichment chip was also ordered from Agilent Inc., USA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to eukaroytes, some patterns in genome size have been discussed ( Lynch and Conery 2003 ; Daubin and Moran 2004 ; Lynch 2004 ). Additionally, a handful of studies have analyzed genome size in connection to other parameters such as indels ( Pettersson et al 2009 ), transposon content ( Kidwell 2002 ; Elliott and Gregory 2015a ; Canapa et al 2016 ), average intron length ( Deutsch and Long 1999 ; Zhu et al 2009 ) or total intron length ( Elliott and Gregory 2015b ). Despite these advances, none of these studies have estimated the amount of the genome that is genic (exonic plus intronic, including noncoding) based on independent examination of single genomes and without averaging over a whole kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Besides cervical cancer, HPV infection has also been etiologically associated and implicated with the development of other anogenital cancers (vulva, vagina, anus and penis) [58,59,60]. An estimated 85% of anal cancers and approximately a half of the vulvar, vaginal and penile cancers are attributable to HPV [61,62]. However, apart from the many studies that associated HPV with anogenital cancers, little is known about how HPV actually contributes to the development of these cancers [61].…”
Section: Other Anogenital Cancersmentioning
confidence: 99%